2022
DOI: 10.1101/2022.07.18.500453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An integrase clade that repeatedly targets prophage late genes, yielding helper-embedded satellites

Abstract: Satellites are mobile genetic elements that rely on helper phages for their mobilization. The many known satellite-helper interactions are trans-regulatory, with gene products from one partner modulating the nucleic acid or protein activities of the other. We discovered a satellite type with a more intimate cis-regulatory configuration: integrated within, and co-oriented with, a late gene of its lambdoid helper prophage. This helper-embedded satellite (HES) configuration would delay expression of the interrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The post-processing automatic analysis of MacSyFinder's output solves these issues only partially. For instance, while this manuscript was being submitted, a preprint showed that satellites can integrate inside prophages ( 47 ), which poses an even more difficult scenario to accurately distinguish these elements from prophages. Future work will be needed to assess the ability of our approach to correctly assign such cases.…”
Section: Discussionmentioning
confidence: 99%
“…The post-processing automatic analysis of MacSyFinder's output solves these issues only partially. For instance, while this manuscript was being submitted, a preprint showed that satellites can integrate inside prophages ( 47 ), which poses an even more difficult scenario to accurately distinguish these elements from prophages. Future work will be needed to assess the ability of our approach to correctly assign such cases.…”
Section: Discussionmentioning
confidence: 99%
“…The post-processing analysis we perform using the output of MacSyFinder is important in diminishing these issues, but does not always solve it. For instance, while this manuscript was being submitted, a preprint showed that satellites can integrate inside prophages (45), which poses an even more difficult scenario to accurately distinguish these elements from prophages. Future work will be needed to assess the ability of our approach to correctly assign such cases.…”
Section: Discussionmentioning
confidence: 99%